2013
DOI: 10.1289/isee.2013.p-2-13-16
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and consequences of global DNA methylation in cord blood and at three years

Abstract: DNA methylation changes have been implicated in many common chronic diseases leading to the hypothesis that environmental and age-related DNA methylation changes within individuals are involved in disease etiology. Few studies have examined DNA methylation changes within an individual over time and all of these studies have been conducted in adults. Here, we aim to characterize how global DNA methylation changes from birth to age three within a longitudinal birth cohort study and to determine whether there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The association between maternal prepregnancy overweight and obesity and offspring BMI, which persists after adjustment for genetic and lifestyle factors, supports previous research describing intergenerational inheritance of metabolic outcomes beyond the inheritance of genetic sequence variants and learned behavior. Although the mechanism underlying fetal programming of obesity is not fully understood, both animal and human models examining the fetal overnutrition hypothesis have supported a possible epigenetic link between maternal and offspring adiposity . Numerous genomic regulatory mechanisms have been implicated in the intergenerational epigenetic inheritance of metabolic disease, including nuclear and ribosomal DNA methylation, histone modifications, and noncoding microRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between maternal prepregnancy overweight and obesity and offspring BMI, which persists after adjustment for genetic and lifestyle factors, supports previous research describing intergenerational inheritance of metabolic outcomes beyond the inheritance of genetic sequence variants and learned behavior. Although the mechanism underlying fetal programming of obesity is not fully understood, both animal and human models examining the fetal overnutrition hypothesis have supported a possible epigenetic link between maternal and offspring adiposity . Numerous genomic regulatory mechanisms have been implicated in the intergenerational epigenetic inheritance of metabolic disease, including nuclear and ribosomal DNA methylation, histone modifications, and noncoding microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Extending the Barker hypothesis that fetal programming because of maternal undernutrition contributes to offspring obesity and CVD , maternal obesity leads to fetal overnutrition, which may also contribute to deleterious cardiometabolic outcomes in the offspring . Fetal programming and epigenetic inheritance are potential mechanisms . Although many studies have demonstrated a robust association between maternal and offspring obesity , little is known about how this association persists beyond young adulthood or changes over an offspring’s lifetime in excess of genetic variation and learned lifestyle behaviors .…”
Section: Introductionmentioning
confidence: 99%
“…Since first publishing our results on NR3C1, we have moved beyond gene‐specific analyses to an analysis of total genome‐wide methylation, specifically methylation at 431,048 CpG dinucleotides spanning >20,000 genes as represented on the Illumina 450 Methylation BeadChip. In this study, we analyze mean global methylation, which has been proposed as a biomarker for disease risk (Choi et al, ; Liao et al, ; Cash et al, ) and also may be reflective of shared factors that confer long‐term effects on health (Herbstman et al, ). (Choi et al, ; Liao et al, ; Cash et al, ; Gomes et al, ; Iwasaki et al, ; Zhao et al, ; Herbstman et al, ; Kuchiba et al, )…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have used mean global methylation to investigate different aspects of health. Studies of human blood samples have documented consistent, age‐related changes in mean global methylation (Gomes et al, ; Herbstman et al, ), an association with insulin resistance as a hallmark of type 2 diabetes (Zhao et al, ), and an association with endogenous sex hormones in women (Iwasaki et al, ). There is an hypothesis for the development of cancer, supported by several studies, that global hypomethylation may cause genomic instability leading to cancer (Choi et al, ; Liao et al, ; Cash et al, ; Kuchiba et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation